The Effects of Perceived Social Support, Family Climate, and Adult Attachment Styles on Digital Game Addiction in Esports Players - Yılmaz, Beyza; Özkan, Yasemin (Addicta: The Turkish Journal on Addictions, 2022)
There have been many different game designs that users find suitable and numerous devices on which various games can be played. The development of digital games over the last 30 years has led to the creation of electronic sports . The main purpose of this study is to examine the relationship between electronic sports players’ perceived social support, family climate, adult attachment styles, and game addiction. The present study examined the game addiction levels of 211 Turkish electronic sports players who are members of the university electronic sports societies in Ankara. The majority of the participants in this research are male and gamer-type players. Players play games almost every day of the week (38.9%), spend 2–4 hours a day on games (50.7%), and watch electronic sports streams (49.8%) for an hour in a day. Half of the players (57.3%) earn an income from the games they play. Simple linear regression analysis indicated that having a fearful attachment style and playing frequently had a significant impact on game addiction.